THE INFLUENCE OF RESOURCE EMPOWERMENT MANAGEMENT HUMAN TO EMPLOYEE PERFORMANCE AT BANDUNG REGENCY PUBLIC WORKS OFFICE - Ramdan, Deden (Jurnal Riset Bisnis dan Manajemen, 2023)
This research is based on the existence of a problem of low employee performance in the Public Works Office of Bandung City. The purpose of this study is to find, develop and apply data and information about the influence of Human Resources Empowerment on Employee Performance in the Public Works Office of Bandung City. Researchers used a quantitative approach using associative research type. Data collection techniques using the method of observation, interviews and distributing questionnaires using saturated sampling techniques which were distributed to 31 respondents and literature studies. The results show that Empowerment of Human Resources had an effect on the performance of the employees of the Bandung Public Works Office, while 51.3% came from other variables. undefined. The results of interviews and observations show that there is an adequate influence between the empowerment of human resources on performance